2012
DOI: 10.1371/journal.pone.0045457
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the Veil of Morality: Choice Blindness and Attitude Reversals on a Self-Transforming Survey

Abstract: Every day, thousands of polls, surveys, and rating scales are employed to elicit the attitudes of humankind. Given the ubiquitous use of these instruments, it seems we ought to have firm answers to what is measured by them, but unfortunately we do not. To help remedy this situation, we present a novel approach to investigate the nature of attitudes. We created a self-transforming paper survey of moral opinions, covering both foundational principles, and current dilemmas hotly debated in the media. This survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
146
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 45 publications
(29 reference statements)
14
146
0
Order By: Relevance
“…However, we tried to eliminate this possibility by including attention checks in our studies, which allowed us to exclude some participants for not attending to the study materials. A second issue with online data collection is that it makes for a less compelling choice blindness manipulation than when a survey inexplicably changes responses (Hall et al, 2012) or when one flavor of jam is magically replaced by another (Hall et al, 2010). Nevertheless, we obtained relatively low rates of detection of our manipulations, which suggests that online data collection is a valid way to study choice blindness (see also Johansson, Hall, Gulz, Haake, & Watanabe, 2007).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, we tried to eliminate this possibility by including attention checks in our studies, which allowed us to exclude some participants for not attending to the study materials. A second issue with online data collection is that it makes for a less compelling choice blindness manipulation than when a survey inexplicably changes responses (Hall et al, 2012) or when one flavor of jam is magically replaced by another (Hall et al, 2010). Nevertheless, we obtained relatively low rates of detection of our manipulations, which suggests that online data collection is a valid way to study choice blindness (see also Johansson, Hall, Gulz, Haake, & Watanabe, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Although some variables, like the type of decision, the manner in which the manipulation occurs, and other between-experiment variables, seem to produce different rates of blindness, choice blindness has been shown to be robust across a variety of domains. Participants' blindness rates have been remarkably high in studies of their political and moral attitudes (53 %; Hall, Johansson, & Strandberg, 2012), financial decision making (63 %;McLaughlin & Somerville, 2013), and even their reported histories of criminal and norm-violating behavior (8 %-10 %; Sauerland et al, 2013).…”
Section: Choice Blindnessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is more worrying that there is evidence of the same pattern in our moral judgments. Hall et al (2012) found evidence of the same choice blindness and confabulation when people were given false feedback about how they had filled in a questionnaire asking moral questions. They gave participants either 12 statements of moral principles or 12 concrete applications of those principles and then asked them to indicate if they agree or disagree on a nine-point scale.…”
Section: Choice Blindnessmentioning
confidence: 95%
“…Amongst other things, they checked for response time, length of statement, word frequency checks for markers of certainty, unfilled pauses, laughter, the use of the past vs. present tense, the use of first vs. third person, emotional content and word length. In later studies conducted by the same research team, Hall et al (2010Hall et al ( , 2012 even allowed participants to report if they had been aware of their confabulations once they have been informed that they must have been confabulating. Despite giving participants the opportunity to retrospectively report uncertainty once they know that their explanations cannot be accurate, the vast majority of participants still indicated that they had been totally unaware that they were confabulating.…”
Section: The Markers Of Certainty Objectionmentioning
confidence: 99%